Media Development Of Miniature Places Of Worship in Learning Pancasila Education in Class IV Public Elementary School 7 Palembang - Anugrah Tanbayu; Lian, Bukman; Aryaningrum, Kiki (PGMI IAIN Lhokseumawe, 2024)
Based on the problems at SD Negeri 7 Palembang, the lack of use of media in learning Pancasila education makes it difficult for students to understand Bhinneka Tunggal Ika material about places of worship. This research aims to produce valid and practical miniature learning media for places of worship. The type of research method used is Research and Development (R&D) with the ADDIE model. The development of learning media for miniature places of worship in class IV Pancasila education learning at SD Negeri 7 Palembang has produced learning media products that have been declared valid by media, language and material experts. The results of the research on Miniature Media for Worship Places were declared valid with an average result of 90.20% in the